2009
DOI: 10.1111/j.1469-1795.2009.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Oil industry, wild meat trade and roads: indirect effects of oil extraction activities in a protected area in north‐eastern Ecuador

Abstract: Starting in 1994, a wholesale wild meat market developed in north-eastern Ecuador, involving Waorani and Kichwa people in the area of influence of a road built to facilitate oil extraction within Yasun´ı National Park. Between 2005 and 2007, we recorded the trade of 11 717 kg of wild meat in this market, with pacas Cuniculus paca, white-lipped peccaries Tayassu pecari, collared peccaries Pecari tajacu and woolly monkeys Lagothrix poeppiggi accounting for 80% of the total biomass. Almost half of the wild meat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 24 publications
0
133
0
8
Order By: Relevance
“…Previous studies in the Amazon have mainly focused on remote, rural settings (e.g., Peres and Nascimento 2006, Parry et al 2009, Suárez et al 2009), neglecting the consumption of urban and periurban locations (but see Baía-Júnior et al 2010, Parry et al 2014. Second, no assessment of a diverse set of beliefs, attitudes and social norms as drivers of http://www.ecologyandsociety.org/vol20/iss4/art21/ Several indigenous territories (Javari is the largest) in approximately 122,000 km² of well-preserved seasonally flooded and "terra firme" forests Sources of domestic meat Local production: chicken and chicken eggs in household production and small farms, small production of cattle milk and pork Imported: frozen chicken (southern Brazil), beef (Putumayo region)…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the Amazon have mainly focused on remote, rural settings (e.g., Peres and Nascimento 2006, Parry et al 2009, Suárez et al 2009), neglecting the consumption of urban and periurban locations (but see Baía-Júnior et al 2010, Parry et al 2014. Second, no assessment of a diverse set of beliefs, attitudes and social norms as drivers of http://www.ecologyandsociety.org/vol20/iss4/art21/ Several indigenous territories (Javari is the largest) in approximately 122,000 km² of well-preserved seasonally flooded and "terra firme" forests Sources of domestic meat Local production: chicken and chicken eggs in household production and small farms, small production of cattle milk and pork Imported: frozen chicken (southern Brazil), beef (Putumayo region)…”
Section: Introductionmentioning
confidence: 99%
“…Among those mammals, most were ungulates (36-40%) and rodents (34-38%), with primates representing fewer (13-19%) carcasses (Jerozolimski and Peres 2003). Bushmeat markets in the Amazon are heavily dominated by peccaries and paca, which in one study represented 36.9% and 28.4% of records and 47.9% and 20.6% of biomass, respectively (Suarez et al 2009). More specific information on the hunted populations are beyond the scope of this report, but their status assessments are synthesized elsewhere for key animals of the African rain forest (Bakarr et al 2001) and the Amazon (Peres and Palacios 2007).…”
Section: Game Species Characteristicsmentioning
confidence: 99%
“…Hunters can be either from the area where the animals are harvested, or immigrants that are brought there by economic opportunities such as logging or oil exploration (Suarez et al 2009). For instance, in Sarawak, Bennett found that bushmeat was present in 29% of meals in the interior, but in 49% of meals in logging camps (Bennett et al 2007).…”
Section: Hunter Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…ILs may be subject to future changes in their patterns of land use, as their indigenous populations grow and make greater demands on natural resources as sources of livelihood. Many ILs have been affected by varying degrees of impacts from illegal logging (Gascon et al 2000;Laurance et al 2001;Schwartzman & Zimmerman, 2005), illegal colonization and ranching (Laurance et al 2001), fires (Adeney et al 2009), hunting (Suárez et al 2009), illegal gold mining (Schwartzman & Zimmerman 2005) and other forms of encroachment with or without consent of their indigenous habitants. In addition to these threats, ILs and PAs from Brazilian Amazon have also been affected by large infrastructure projects, such as hydroelectric dams (Fearnside 1995(Fearnside , 2002, oil and gas projects (Finer et al 2008;Suárez et al 2009), mining (Laurance 1998;Laurance et al 2001), roads (Nepstad et al 2001;Fearnside 2007) and the indirect effects of these activities (Suárez et al 2009).…”
Section: Deforestation and Conservation In Watersheds Of The Amazon: mentioning
confidence: 99%